The GENIUS Web Portal - Andronico, G.; Barbera, R.; Falzone, A.; Lo Re, G.; Pulvirenti, A.; Rodolico, A. (Methods of Information in Medicine, 2005)
Objective: The development of computational Grids is making huge amounts of computing power and data storage available for a lot of scientific applications.At this stage of development, the use of the Grid is mainly based on Command Line Interface (CLI) tools that are not very friendly and can be considered an obstacle to the use of these powerful tools. The objective of this paper is to present a solution to this problem.Methods: To ease the access of new users to the grid the GENIUS (Grid Enabled web eNvironment for site Independent User job Submission) grid portal has been jointly developed by INFN and NICE within the context of both the Italian INFN Grid and the European DataGrid Projects. Here we devote particular care to the description of job creation and submission and the services for transparent access to user’s data and applications.Results: Using GENIUS, the obstacle of complicated CLI can be overtaken and simple web interfaces can be built for specific user communities and applications. Here we show examples in the field of bio-medical applications.Conclusions: The use of Grid can be made easy with the use of Grid portals such as GENIUS.
Keywords: Grid computing; Grid portals; problem-solving environments; bio-informatics